Taxes in an E-Commerce Generation - David R. Agrawal; William F. Fox (Center for Economic Studies and ifo Institute (CESifo), 2016)
Rapid growth in e-commerce has altered the ability of jurisdictions to enforce commodity taxes on a destination basis. This results in different effective tax rates depending on the way in which goods and services are purchased and the characteristics of both the products and the sellers. We discuss the arguments for the destination principle as the appropriate place-of-taxation rule for consumption taxation of cross-border trade. We analyze various recent reforms to the Value Added Tax in the European Union in response to e-commerce. We then examine various policy options in the United States – maintaining the status quo, changing nexus rules, states adopting information reporting, and national reforms that require firms to remit taxes regardless of physical presence – and relate them to the recent European reforms. We conclude based on our analysis and the recent European Union experience that reforms at the national level appear to be the important next step to enforcing commodity taxes at destination in the U.S.
Keywords: H20; H70; L81; R50; 330; destination taxation; origin taxation; commodity taxes; online shopping; e-commerce; tax competition; digital products